Electrospun Gelatin Scaffolds with Incorporated Antibiotics for Skin Wound Healing - Katarina Virijević; Marko Živanović; Jelena Pavić; Luka Dragačević; Biljana Ljujić; Marina Miletić Kovačević; Miloš Papić; Suzana Živanović; Strahinja Milenković; Ivana Radojević; Nenad Filipović (MDPI AG, 2024)
Recent advances in regenerative medicine provide encouraging strategies to produce artificial skin substitutes. Gelatin scaffolds are successfully used as wound-dressing materials due to their superior properties, such as biocompatibility and the ability to mimic the extracellular matrix of the surrounding environment. In this study, five gelatin combination solutions were prepared and successfully electrospun using an electrospinning technique. After careful screening, the optimal concentration of the most promising combination was selected for further investigation. The obtained scaffolds were crosslinked with 25% glutaraldehyde vapor and characterized by scanning electron microscopy, energy-dispersive X-ray spectroscopy, and Fourier-transform infrared spectroscopy. The incorporation of antibiotic agents such as ciprofloxacin hydrochloride and gentamicin sulfate into gelatin membranes improved the already existing antibacterial properties of antibiotic-free gelatin scaffolds against Pseudomonas aeruginosa and Staphylococcus aureus. Also, the outcomes from the in vivo model study revealed that skin regeneration was significantly accelerated with gelatin/ciprofloxacin scaffold treatment. Moreover, the gelatin nanofibers were found to strongly promote the neoangiogenic process in the in vivo chick embryo chorioallantoic membrane assay. Finally, the combination of gelatin's extracellular matrix and antibacterial agents in the scaffold suggests its potential for effective wound-healing treatments, emphasizing the importance of gelatin scaffolds in tissue engineering.